2018
DOI: 10.4274/tnd.12058
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Changes and Their Prognostic Effect in Patients with Acute Ischemic Stroke without Cardiac Etiology

Abstract: ÖzOriginal Article / Özgün Araştırma Amaç: Akut iskemik inme, EKG sonuçları ve kardiyak enzim düzeyleri üzerinde etkili olmakla birlikte mekanizması açık bir şekilde belirlenememiştir. Amacımız akut iskemik inmede EKG ve kardiyak enzim değişikliklerini incelemek ve bu değişiklikler ile inme lokalizasyonu ve prognoz arasındaki ilişkiyi araştırmaktır. Gereç ve Yöntemler:Çalışma 241 akut iskemik inme hastalarını içermektedir., Çalışmaya kardiak aritmi ve inme öyküsü olmayanlar ile EKG ritmi ve süresini etkileyen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Acute chest pain conditions have a quite common symptoms and ECG is one of the most important diagnostic tool used in the differential diagnosis of these disorders (2). Many reasons, such as coronary artery diseases, pericardial diseases, ischemic stroke, electrolyte disturbances, and intoxications, can present with specific or nonspecific findings on ECG (16)(17)(18)(19)(20). Clinical conditions that decrease venous return to the thoracic cavity, disrupt perfusion, and increase systemic vascular resistance cause ECG changes.…”
Section: Discussionmentioning
confidence: 99%
“…Acute chest pain conditions have a quite common symptoms and ECG is one of the most important diagnostic tool used in the differential diagnosis of these disorders (2). Many reasons, such as coronary artery diseases, pericardial diseases, ischemic stroke, electrolyte disturbances, and intoxications, can present with specific or nonspecific findings on ECG (16)(17)(18)(19)(20). Clinical conditions that decrease venous return to the thoracic cavity, disrupt perfusion, and increase systemic vascular resistance cause ECG changes.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ECG changes have a significant relationship with aging [49]; additionally, the ECG abnormalities are regularly seen in stroke patients [50,51]. Many studies reported that the most common ECG abnormalities associated with acute stroke are arrhythmia, prolonged QTc and T wave and U wave abnormalities [19,[52][53][54][55]. Accordingly, we noticed the prolonged QTc in the stroke group, including both male and female subjects, with the overall mean value of the QTc greater than 450 milliseconds.…”
Section: Discussionmentioning
confidence: 99%